Analysis on the MRI and BAEP Results of Neonatal Brain With Different Levels of Bilirubin - Zhongxing Lu; Zhongxing Lu; Shouling Ding; Fen Wang; Haitao Lv (Frontiers in Pediatrics, 2022)
BackgroundTo explore whether there is abnormality of neonatal brains' MRI and BAEP with different bilirubin levels, and to provide an objective basis for early diagnosis on the bilirubin induced subclinical damage on brains.MethodsTo retrospectively analyze the clinical data of 103 neonatal patients, to conduct routine brain MRI examination and BAEP testing, and to analyze BAEP and MRI image results of the neonatal patients, who were divided into three groups based on the levels of total serum bilirubin concentration (TSB): 16 cases in mild group (TSB: 0.0–229.0 ěmol/L), 49 cases in moderate group (TSB: 229.0–342.0 ěmol/L), and 38 cases in severe group (TSB ≥ 342.0 ěmol/L).ResultsWe found the following: A. Comparison of the bilirubin value of the different group: The bilirubin value of the mild group is 171.99 ± 33.50 ěmol/L, the moderate group is 293.98 ± 32.09 ěmol/L, and the severe group is 375.59 ± 34.25 ěmol/L. The comparison of bilirubin values of the three groups of neonates (p < 0.01) indicates the difference is statistically significant (p < 0.01). B. The weight value of the <2,500 g group is 2.04 ± 0.21 and the ≥2,500 g group is 3.39 ± 0.46; the weight comparison of the two groups indicates that the difference is statistically significant (p < 0.01). C. Comparison of the abnormal MRI of the different groups: The brain MRI result's abnormal ratio of the mild group is 31.25%, the moderate group is 16.33%, and the severe group is 21.05%, but the comparison of brain MRI results of the three neonates groups indicates that the difference is not statistically significant (p > 0.05). D. Comparison of abnormal MRI signal values of globus pallidus on T1WI in different groups: 1. The comparison of normal group signal values with that of mild group (p < 0.05), with that of moderate group, and with that of severe group (p < 0.01) indicates that the difference is statistically significant.ConclusionAt low level of bilirubin, central nervous system damage may also occur and can be detected as abnormality by MRI and BAEP. Meanwhile, MRI and BAEP can also provide early abnormal information for the judgment of central nervous system damage of the children with NHB who have no acute bilirubin encephalopathy (ABE) clinical features, and provide clues for early treatment and early intervention.